Pengaruh Terapi Relaksasi Otot Progresif dalam Penurunan Skala Nyeri pada Lansia dengan Hipertensi di Wilayah Kerja Puskesmas Siulak Gedang Tahun 2024 - Rosiska, Evan (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Hypertension in the elderly is characterized by an increase in systolic and diastolic blood pressure, namely ≥ 140/90 mmHg consistently and often occurs in the elderly aged ≥ 55 years. Progressive Muscle Relaxation is a technique that can relax tense muscles and create a relaxed feeling so that it can lower blood pressure. This study aims to determine the effect of progressive muscle relaxation on reducing the pain scale in middle-aged elderly with hypertension in the Siulak Gedang Health Center work area in 2024. The research design used was one group pretest and post-test design with a purposive sampling method, namely 16 middle-aged elderly respondents in the Siulak Gedang Health Center work area. The instruments used in data collection were SOP, observation sheets, stethoscopes, sphygmomanometers. The results of the study showed that there was an effect of progressive muscle relaxation therapy on reducing the pain scale in hypertensive patients with the results of the paired sample t-test obtained a p-value = 0.000, because the p-value <0.05.